BIM in Construction: Benefits, Challenges, and Development Trends - Thang Ngoc Nguyen (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Building Information Modeling (BIM) is a transformative technology driving digital innovation in the construction industry. Beyond a 3D design tool, BIM serves as a comprehensive data integration platform that facilitates seamless collaboration among stakeholders throughout the entire project lifecycle - from design and construction to operation. This article provides an overview of BIM, exploring its applications, benefits, challenges, and future development trends. Currently, BIM is extensively utilized in architecture, civil engineering, MEP (mechanical, electrical, and plumbing), and infrastructure management. Its advanced simulation and analytical capabilities help minimize design errors, optimize costs, accelerate project timelines, and enhance construction quality. However, challenges such as high initial investment, workforce training demands, and integration with legacy systems remain significant barriers to widespread adoption. Despite these obstacles, ongoing technological advancements and supportive policies are solidifying BIM’s role as an industry standard. Looking ahead, BIM is expected to integrate with Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), and the Internet of Things (IoT), fostering a digital ecosystem that enhances efficiency and sustainability in construction.
Keywords: Building Information Modeling; Construction Technology; Digital Transformation; Project Management; Sustainable Construction